Proteomic Profiling Exosomes from Vascular Smooth Muscle Cell. Issue 5 (5th June 2018) - Qiu, Hong; Shi, Songshan; Wang, Shunchun; Peng, Hong; Ding, Shi‐Jian; Wang, Lianchun
Abstract : Purpose: Vascular smooth muscle cells (VSMC) and endothelial cells (EC) communicate mutually to coordinate vascular development and homeostasis. Exosomes are emerging as one type of the mediators involved in this communication. Characterizing proteins in the exosomes is the critical first step in understanding how the VSMC‐EC crosstalk is mediated by exosomes. Experimental design: The proteins in the human VSMC‐derived exosomes are profiled using nanoLC‐MS/MS based proteomics. The identified proteins are subjected to gene ontology analysis. The VSMC‐derived exosomes are also assessed for proangiogenic activity in vivo. Results: Four hundred and fifty‐nine proteins are identified in the VSMC‐derived exosomes. Gene ontology analysis revealed that the exosome proteins are involved in 179 cellular components, 120 molecular functions, and 337 biological processes, with cell–cell adhesion and platelet activation/coagulation ranked at the top. VSMC‐derived exosomes do not display a proangiogenic activity in the in vivo angiogenesis assay, suggesting that the major function of VSMC‐derived exosomes is to maintain vessel homeostasis. Conclusion and clinical relevance: The analyses obtained a systematic view of proteins in the VSMC‐derived exosomes, revealed the potential regulatory functions of the exosome in VSMC‐EC communication, and suggest that dysregulation of VSMC‐derived exosome‐mediated functions may disturb vessel homeostasis thereby contributing to vascular diseases.